Patients' perspectives on adherence to cardiovascular screening consultation and lifestyle changes - Julie Katrine Karstensen; Ann Bremander; Katrine Engholm Nielsen; Jette Primdahl; Jeanette Reffstrup Christensen (BMC, 2024)
Abstract Background Rheumatoid arthritis (RA) poses a significant health burden, with patients facing a twofold higher risk of cardiovascular diseases compared to the general population. As a results, the international recommendations set forth by the European Alliance of Associations for Rheumatology, advocate for a structured cardiovascular (CV) risk management and adherence to a healthy lifestyle for patients with RA. Unhealthy lifestyle factors not only impact overall health but also worsen inflammation and hinder treatment response in patients with RA Despite these recommendations, there remains a knowledge gap regarding patients' attitudes towards screening participation and lifestyle changes. Therefore, the aims of this study were firstly to explore the perspectives of patients with rheumatoid arthritis on participation and adherence to cardiovascular screening. Secondly, to explore patients' perspectives on lifestyle changes. Methods Semi-structured interviews based on a hermeneutic approach were conducted. The analysis was guided by qualitative content analysis, employing an inductive approach. Results Nine women and seven men, aged 47 to 76 years, diagnosed with RA, and who had attended at least one CV screening session, took part in the study. Two primary themes, along with four sub-themes, emerged from the analysis. The first main theme, Accepting an offer, encompassed the sub-themes of Engagement in the screening consultation and Risk awareness, reflecting participants' views on their involvement in, and commitment to, CV screening. The second theme pertained to participants' perspectives on lifestyle changes: Living with a chronic disease and embracing changes, described through the sub-themes of Motivation for lifestyle changes and Strategies to achieve lifestyle changes. Conclusion Motivations for taking part in the screening differed among the participants, ranging from simply accepting an invitation to joining as a proactive precaution. In general, there was unanimous agreement among the participants that the screening proved to be a positive encounter. While it may not have immediately prompted significant lifestyle alterations, it did enhance their awareness of risks and underscored the significance of maintaining a healthy lifestyle. Overall, the individual guidance and support for patients with rheumatoid arthritis should entail awareness of CV risk combined with support to lifestyle changes the participants want to pursue.